Optimizing local wisdom-based learning through digital media - Fadhilah, Ayu; Sumarni, Sri; Hartono,; Syarifuddin, (Indonesian Research Journal in Education |IRJE|, 2025)
This paper is a literature review that aims to explore the optimization of learning based on local wisdom through the use of digital media in learning. In the increasingly developing digital era, the preservation of local culture faces great challenges in the midst of global information dominance. This literature review discusses optimizing learning based on local wisdom by using digital media to improve the quality of education The method used in this study is Narrative Literature Review (NLR). The literature studied shows that the use of technology in learning local wisdom is able to increase student engagement, deepen cultural understanding, and strengthen local identity among the younger generation. The technology media used include e-modules, AR, VR, Animation Videos and websites. This study concludes that learning technology media has great potential in integrating local arigan into education. As long as it is carried out in a planned and thorough manner.